Evolutionary and biogeographical patterns of barnacles from deep‐sea hydrothermal vents - Santiago Herrera; Hiromi Watanabe; Timothy M. Shank (Molecular Ecology, 2015)
The characterization of evolutionary and biogeographical patterns is of fundamental importance to identify factors driving biodiversity. Due to their widespread but discontinuous distribution, deep‐sea hydrothermal vent barnacles represent an excellent model for testing biogeographical hypotheses regarding the origin, dispersal and diversity of modern vent fauna. Here, we characterize the global genetic diversity of vent barnacles to infer their time of radiation, place of origin, mode of dispersal and diversification. Our approach was to target a suite of multiple loci in samples representing seven of the eight described genera. We also performed restriction‐site associated DNA sequencing on individuals from each species. Phylogenetic inferences and topology hypothesis tests indicate that vent barnacles have colonized deep‐sea hydrothermal vents at least twice in history. Consistent with preliminary estimates, we find a likely radiation of barnacles in vent ecosystems during the Cenozoic. Our analyses suggest that the western Pacific was the place of origin of the major vent barnacle lineage, followed by circumglobal colonization eastwards through the Southern Hemisphere during the Neogene. The inferred time of radiation rejects the classic hypotheses of antiquity of vent taxa. The timing and the mode of origin, radiation and dispersal are consistent with recent inferences made for other deep‐sea taxa, including nonvent species, and are correlated with the occurrence of major geological events and mass extinctions. Thus, we suggest that the geological processes and dispersal mechanisms discussed here can explain the current distribution patterns of many other marine taxa and have played an important role shaping deep‐sea faunal diversity. These results also constitute the critical baseline data with which to assess potential effects of anthropogenic disturbances on deep‐sea ecosystems.